The tribological characteristics of the cactus and mineral oil blends using four-ball tribotester - Hassan, M. (Penerbit UTM Press, 2016)
The oil derived from vegetables has been seen as an alternative to mineral oils for lubricants because of certain inherent technical properties, renewable source and their abilities to biodegrade. Vegetable oil is known to have a high viscosity index with a higher lubricity value compared to mineral oil. Despite its potentiality as a candidate alternative, vegetable oil has several limitations. It has a low wear resistance, and it is highly sensitive to temperatures with tribological characteristics. The majority of technical solutions, including additivation, chemical alterations, and blending, are being proposed as means of overcoming the listed limitations. This study seeks to investigate the characteristics of cactus oil with respect to its use as a bio-lubricant as well as the characteristics of environmentally friendly vegetable oil when they are mixed with mineral oils as alternative oil for petroleum, using the four-ball tribotester. The volumetric blending ratio was varied (20% to 80%) and these blends were performed at 1200 rpm, for one hour, with 40 kg of load at a temperature of 75ºC (ASTM D4172-B) standard. According to the results, it was found that the lowest wear scar diameter was 431.23μm, which was identified in the blend of 20% cactus oil with 80% mineral oil which symbolized by (CC20%), compared to that of neat cactus oil at 669.16 μm and mineral oil at 546.46 μm.In addition, the result also indicates that a 80% addition of cactus oil, the coefficient of friction tends to decrease compared to the values of neat cactus oil. Finally, it is concluded, the blends of cactus oil with commercial lubricant oil have better performance compared to commercial lubricant oil or neat cactus oil.